Atomic force microscopy (AFM) analysis of cleaned and fouled nanofiltration membranes. (10th August 2009) - Al-amoudi, A.; Wright, C.; Williams, P.; Lovitt, R.W., A. Al-Hobiab
In membrane process industries, membrane cleaning is one of the most important concerns from both economical and scientific points of view. Surfaces roughness and phase angle of virgin and fouled membranes were measured and compared before and after chemical cleaning by using atomic force microscopy (AFM). Correlations between the data obtained by this technique (AFM) with the flux and rejection have also been discussed.